A proposed segmented precast concrete spherical cap: geometry, structural stability and construction - Kenawy, Maha (AUC Knowledge Fountain, 2015)
This study proposes the design and construction of a concrete spherical cap composed of uniformly-shaped precast doubly-curved panels based on spherical division techniques. A numerical structural analysis is conducted to study the failure behavior of the segmented structure and the capacity of the joints by using finite element modeling techniques to model the concrete material behavior, boundary conditions and intermediate joints of the precast panels. An experimental analysis is conducted to verify the capacity of the structure and the reliability of the modeling techniques, and to study the feasibility of the proposed panel prefabrication and assembly method. The results of this study demonstrate that the proposed precast system and connection design perform efficiently when compared to the monolithically-cast counterpart, particularly under uniform loading conditions. Additional insights on the properties and solution parameters of finite element modelling of concrete shell structures are presented based on the structural analysis of this work. The study concludes the ability of the proposed geometric design and construction method to enhance the prefabrication and construction efficiency with little effect on the structural capacity within the context of the selected geometry and conducted load tests, and recommends further parameters to study for design and construction optimization.